PERAN DUKUNGAN ORGANISASI TERHADAP KINERJA : ANALISIS PERAN KETERLIBATAN DOSEN PERGURUAN TINGGI - Erni Taruli Pebrina (Universitas Insan Pembangunan Indonesia, 2021)
This study aimed to measure the effect of perceived organizational support on performance of private higher education lecturers in Tangerang which are mediated by lecturer engagement. Data collection was done by simple random sampling via electronic to the private higher education lecturer population in Tangerang. The returned and valid questionnaire results were 98 samples. Data processing was used SEM method with SmartPLS 3.0 software. The results of this study concluded that perceived organizational support have a positive and significant effect on the lecturer performance, both directly and indirectly through mediating lecturer engagement. This new research proposed a model for building performance among the private higher education lecturers in Tangerang through enhancing perceived organizational support with lecturer engagements a mediator. This research could pave the way to improve lecturer readiness in facing the era of education 4.0.Keywords: Engagement, perceive organizational support, performance.